2014
DOI: 10.18632/oncotarget.2502
|View full text |Cite|
|
Sign up to set email alerts
|

Paradoxical role of CBX8 in proliferation and metastasis of colorectal cancer

Abstract: The effect of polycomb chromobox (Cbx) proteins in cancer is context-dependent. The Chromobox homolog 8 (CBX8) was originally characterized as a transcriptional repressor, which inhibits cell proliferation in Ink4a-Arf-dependent and -independent manner. However, the role of CBX8 in colorectal cancer remains unknown. Here, we found that high CBX8 expression was associated with a low rate of distant metastasis and good prognosis in CRC patients, even though CBX8 was up-regulated in CRC cell lines and clinical sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 47 publications
4
68
0
Order By: Relevance
“…A recent study showed that depletion of CBX8 delays cell cycle progression and results in the inhibition of proliferation of CRC by the p53 pathway . We wondered whether a similar pathway is involved in UCB when CBX8 is depleted.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A recent study showed that depletion of CBX8 delays cell cycle progression and results in the inhibition of proliferation of CRC by the p53 pathway . We wondered whether a similar pathway is involved in UCB when CBX8 is depleted.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, CBX8 directly binds to the INK4A‐ARF locus to promote cell proliferation and to bypass senescence . Recent reports have shown that CBX8 is positively associated with glioblastoma, colorectal cancer, and leukemia . For example, CBX8 upregulation is associated with TNM staging in esophageal carcinoma, and it acts as a novel DNA repair protein that promotes cell proliferation and protects cancer cells from sensitivity to ionizing radiation or hydrogen peroxide .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferation, invasion and cloning ability of ESCC cells (KYSE2 and KYSE510) were suppressed by silencing CBX8 [40]. Tang et al [41]. found that CBX8 was highly expressed in colorectal cancer tissue, suggesting a poor prognosis and that knockdown of CBX8 would increase the expression of p53 and its downstream effect factors, which would restrain the proliferation of colorectal cancer cells.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…In contrast, low levels of CBX7 mRNA correlate with disease progression and a negative prognosis in bladder carcinoma, while the loss of CBX7 protein expression correlates with a highly malignant phenotype in thyroid cancer, indicating that CBX7 regulates genes involved in cancer progression. Low levels of CBX8 are associated with a poor prognosis and high rate of distant metastasis in colorectal cancer patients . MEL18, the PRC1 subunit, exhibits tumor suppressor activity through inhibition of BMI1 expression .…”
Section: Pcgs Proteins As Diagnostic and Prognostic Biomarkers For Camentioning
confidence: 99%